The impact of corporate donations on third sector organizations: a systematic literature review - Simaens, A.; Abreu, M. E.; Nicolau, I. (Atas 3ª edição da Conferência Internacional do CIRIEC (Centre International de Recherches et d'Information sur l'Economie Publique, Sociale et Coopérative) de Investigação em Economia, 2011)
One of the most prominent problems for third sector organizations is to find sources of funding so that they can fulfill their missions. Among other sources, corporations have played an important, active role in supporting this sector through their social responsibility initiatives. Donations are one of the forms used most. This paper uses a systematic literature review to achieve an understanding of the impacts of corporate donations on third sector organizations. Despite the small amount of literature on this specific topic, key findings indicate that there are, in fact, potential impacts. These can be divided into three categories: resources - impacts on resource dependence and alternative funding sources, growth dynamics - impacts on future donations and growth through networks, and procedures and policies - impacts on internal procedures and policies. The interplay between these impacts is discussed and is the basis for an agenda of further research.